2008
DOI: 10.1111/j.1937-8327.2001.tb00207.x
|View full text |Cite
|
Sign up to set email alerts
|

Instructional Design and Powerful Learning

Abstract: Instructional Design and Powerful LearningI (the fi rst author) have been teaching instructional design (ID) for a decade, and I often start by focusing students' attention on their own learningon what has been very eff ective, what has not, and why. In one exercise, I ask students to refl ect on the nature and causes of their very best and very worst learn ing experiences. In doing this exer cise, I've grown more and more curi ous about the fact that I have been unable in ten years to see a direct link betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
(27 reference statements)
4
6
0
Order By: Relevance
“…Students in this study feel that their instructors who do not have such experience do not always model good ID practice. This fi nding is consistent with the fi nding of Rowland and Divasto's ( 2001 ) study on powerful learning experiences of adult learners. These researchers found that personal interaction with an expert teacher who has a high level of expertise in the domain and who also participates actively in the learning process as a role model is believed to be a powerful learning experience.…”
Section: Addressing Design Judgmentsupporting
confidence: 93%
“…Students in this study feel that their instructors who do not have such experience do not always model good ID practice. This fi nding is consistent with the fi nding of Rowland and Divasto's ( 2001 ) study on powerful learning experiences of adult learners. These researchers found that personal interaction with an expert teacher who has a high level of expertise in the domain and who also participates actively in the learning process as a role model is believed to be a powerful learning experience.…”
Section: Addressing Design Judgmentsupporting
confidence: 93%
“…This is understandable given the younger age group. Factors emphasized here are consistent with those identified in Study 1 (Rowland & DiVasto, 2001): active engagement in authentic settings; personal interaction with mentor/expert teacher; teacher cares about student learning; learner pushed outside comfort zone within safe and supportive environment; support from a peer group; visual reinforcement of points that are spoken; and independence and ability to control one's own learning. Areas where this is not the case include: opportunity for reflection in and on action; motivation to learn; and informal low-pressure environment.…”
Section: Comparison To Previous Studiessupporting
confidence: 75%
“…In our first study (Rowland & DiVasto, 2001), we conducted a series of interviews with a group of eight adult learners. Themes that emerged in terms of factors that were perceived to influence powerful learning included active engagement in authentic settings (i.e., in settings that either represent or approximate environments where knowledge and skill is typically applied), personal interaction with mentor/expert teacher (i.e., with someone who serves as a mentor and who is also an expert teacher), and opportunity for reflection in and on action.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since they were conducted primarily in academic and business settings, previous research studies have not indicated the needs for instructional materials (Albi, 2007;Kay, 2011;Pérez, 2011;Smith, 2009). Some studies, however, have reported financial challenges in the implementation of sound instructional design theories (Parsons, 2008;Rowland & DiVasto, 2001).…”
Section: International Journal Of Academic Research In Progressive Edmentioning
confidence: 99%